PENGARUH KUALITAS PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPERCAYAAN PASIEN DI KLINIK PRATAMA MITRA MULYA KOTA BANDUNG - Anuri R; Yuyus . (Scientia Regendi, 2022)
Background: Health services are an urgent need that must be met immediately. Service quality provides an impetus to service users to establish a bond relationship with service providers. Trust in the use of a product or service, in this case in the form of the service used, is an important factor that needs to be considered by the hospital/clinic. Research objectives: to obtain test results and studies on service quality and employee performance that can affect patient trust at the Mitra Mulya Bandung Pratama Clinic. Method: The design of this type of research used is correlative analytic with a cross-sectional approach consisting of X1 service quality and X2 employee performance on Y Patient Trust. The population and sample of this study were visiting patients with a total sample of 113 people. Data analysis and hypothesis testing used were multiple linear regression analysis, multiple correlation analysis, simultaneous determination coefficient and partial determination coefficient, simultaneous and partial hypothesis testing. Results: The results showed that 65% had poor service quality and 55% of health workers' performance was not good. Simultaneously the variables of service quality and Employee Performance have a positive influence, this can be seen from the tcount of the effect of Employee Performance on patient trust of 6.226. Suggestion: can increase the ability or skills in carrying out their duties, so that the services provided to patients can improve good quality